The Peaceful Teaching Method of Datok Sulaiman in Spreading Islam in Tana Luwu, Indonesia. - Bulu, Bulu; Nuryani, Nuryani; Karim, Abdul Rahim (Nadwa: Jurnal Pendidikan Islam, 2020)
This study discusses the teaching method of Datok Sulaiman in spreading Islam in Tana Luwu, South Sulawesi, Indonesia. This study employed historical and sociological approaches to unpack those research aims. The research findings show that the teachings of Islam transmitted throughout the Tana Luwu region used a peaceful approach without involving any violence with the support of Datok Luwu. Datok Sulaiman mostly used dialogue, Sufistic, and supernatural approaches to spread Islam. Therefore, he could successfully spread Islam in Tana Luwu, including the conversion of XV King Luwu in 1603 which influenced the rapid conversion of Islam in the area.AbstrakStudi ini membahas metode pembelajaran Datok Sulaiman dalam menyebarkan Islam di Tana Luwu. Sulawesi Selatan, Indonesia. Pendekatan yang digunakan adalah pendekatan historis dan sosiologis. Analisis yang digunakan adalah reduksi data, penyajian data, dan penarikan kesimpulan. Hassil penelitian menunjukkan bahwa ajaran Islam berkembang pesat di seluruh wilayah Tana Luwu secara damai tanpa kekerasan berkat peran Datok Sulaiman. Metode pengajaran Islam damai yang digunakan oleh Datok Sulaiman adalah dialog, pembelajran sufisme, dan supranatural. Hal ini berdampak pada adanya dukungan Raja Luwu XV pada 1603 M, sehingga agama Islam berkembang dengan cepat